Richmond, Nemaha County - Bergman, Neil (Kansas State University, The Chapman Center for Rural Studies, 2012)
Richmond, settled by Upland Southerners, was the territorial county seat for Nemaha County. Competition with a twin town and differing opinions on slavery led to the Richmond’s abandonment. This study includes early surveys of Richmond Township and photographs of early settlements.
Neil Bergman, “Richmond, Nemaha County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/99.
Keywords: Nemaha County; Richmond; Seneca; Bogus Legislature; Central City; Cyrus Dolman